2018
DOI: 10.1016/j.bbrc.2017.10.166
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia-mediated transcriptional activation of cytochrome P4501A1 (CYP1A1) and decreased susceptibility to oxygen-mediated lung injury in newborn mice

Abstract: Hyperoxia contributes to the development of bronchopulmonary dysplasia (BPD) in premature infants. In this study, we tested the hypothesis that newborn transgenic mice carrying the human CYP1A1-Luc promoter will display transcriptional activation of the human CYP1A1 promoter in vivo upon exposure to hyperoxia, and that these mice will be less susceptible to hyperoxic lung injury and alveolar simplification than similarly exposed wild type (WT) mice. Newborn WT (CD-1) or transgenic mice carrying a 13.2 kb human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Unsurprisingly, the induction of CYP1A1 function by β-naphthoflavone reduced the classical features of hyperoxic lung injury in mice, as did the transgenic overexpression of the CYP1A1 promoter in newborn mice subjected to hyperoxia. The studies on the CYP1A1 promoter overexpression found that the hyperoxic exposure per se induces the activation of the promoter and the CYP1A1 activity that is responsible for the attenuation of hyperoxic lung injury [29,30]. Further studies extending these initial findings have provided evidence that β-naphthoflavone action is not restricted to CYP1A1, as postnatal administration in CYP1A1-knockout mice induced the expression of CYP1A2 and NAD(P)H quinone oxidoreductase, which led to comparable reduction in lung injury to that in wild-type mice [31].…”
Section: Antioxidative Defense and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Unsurprisingly, the induction of CYP1A1 function by β-naphthoflavone reduced the classical features of hyperoxic lung injury in mice, as did the transgenic overexpression of the CYP1A1 promoter in newborn mice subjected to hyperoxia. The studies on the CYP1A1 promoter overexpression found that the hyperoxic exposure per se induces the activation of the promoter and the CYP1A1 activity that is responsible for the attenuation of hyperoxic lung injury [29,30]. Further studies extending these initial findings have provided evidence that β-naphthoflavone action is not restricted to CYP1A1, as postnatal administration in CYP1A1-knockout mice induced the expression of CYP1A2 and NAD(P)H quinone oxidoreductase, which led to comparable reduction in lung injury to that in wild-type mice [31].…”
Section: Antioxidative Defense and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…The induced hypoxemic conditions in intraperitoneal adhesion development [ 28 , 44 – 46 ] are theorized to disrupt the balance of persistence of the fibrin gel matrix with fibroblast infiltration laying down collagen (a prerequisite to adhesion development) [ 47 ], lower apoptosis through S-nitrosylation of caspase-3 [ 33 ] and lower fibrinolysis [ 48 ], leading to the formation of disarrayed dense tissue. Similarly, hyperoxemia as with oxygen treatment can also cause oxidative stress via an increase in the NADH oxidase and P450 reductase pathway [ 49 ] as shown in Fig. 1 .…”
Section: Pathophysiology Of Adhesion Formationmentioning
confidence: 99%
“…A previous study demonstrated the significant upregulation of NQO1 expression in transgenic mice carrying the human CYP1A1-Luc promoter upon exposure to hyperoxia, and suggested that these mice are less susceptible than wild-type mice to hyperoxia-induced ALI and alveolar simplification (36). In another study, miR-494 was shown to negatively regulate NQO1 and block the Nrf2 signaling pathway, resulting in the acceleration of ALI in rats with sepsis-associated acute respiratory distress syndrome (37).…”
Section: Discussionmentioning
confidence: 97%